Linguistic identity as a cultural phenomenon: Salvador Dali (Journal of Philosophy Culture and Political Science, 2018)
The article discusses the unique linguistic identity, its structure and specific characteristics based on an example of the literary and cinematic genius Salvador Dali. Particular attention is paid to the uniqueness and paradoxical nature of Dali’s unique verbal identity, which is studied as a verbal and aesthetic phenomenon, just like the time that is captured in the word and the cinematography. Based on the fact that the language is not only an essential means of communication but also a symbol of culture, the article discusses the fascinating influence of the Word on the reader / viewer. The authors emphasize that the word and the image are found in an inseparable expressive connection.Key words: language, speech verbal personality, charisma, epatage, paradoxical thinking, thought and verbal activity.